Assesment Sistem Informasi Manajemen Rekam Medis pada Klaim Rawat Jalan BPJS dengan Health Metric Network - Kristiawan, Hedie; Parulian, Adi Anggoro; Firmansyah, Yura Witsqa; Prasaja, Bhisma Jaya (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Health information systems are a priority in supporting Universal Health Coverage (UHC). Yet 65% of WHO member states face challenges in health information system integration, causing losses of up to 300 billion per year. In Indonesia, 35% of BPJS claims are delayed due to incomplete documentation. This study aims to evaluate the Medical Record Management Information System (SIMRM) at West Bandung Private Hospital using the Health Metric Network (HMN) framework. The mix method design was used with a total sampling of 22 medical record staff. Data was collected through questionnaires, interviews and observations. The results show that SIMRM is in the category of